Unheard Women’s Voices: Gender Stereotypes In Khaled Hosseini’s A Thousand Splendid Suns (Journal of Namibian Studies : History Politics Culture, 2022)
Khaled Hosseini’s novel A Thousand Splendid Suns (2007) explores the lives of two women, Mariam and Laila, in Afghanistan during a time of political turmoil and gender inequality. The novel provides an important insight into the unheard voices of Afghan women and sheds light on feminist themes. The paper examines the women’s struggles and experiences are observed in the novel from a feminist perspective, which inspects how they cope with patriarchal societies. The novel highlights the oppressive conditions faced by women in Afghanistan and the limitations placed upon them due to societal norms and expectations. Hosseini illustrates Afghan women’s resilience and strength in the face of immense adversity through Mariam and Laila. The novel gives voice to the unheard experiences of Afghan women and raises awareness about the injustices they endure. Through its exploration of feminism, agency, female solidarity, and intersecting forms of oppression, the novel contributes to a broader understanding of gender inequality and the importance of advocating for women’s rights.